India - Waterstone, Richard (Boston Little, Brown and Co., 1995)
"Describes the main themes in the Hindu, Buddhist, Jain, and other spiritual traditions of India, and explores their points of contact with Western preoccupations"--P. [4] of cover.
Keywords: India -- Religion